1999
DOI: 10.1111/j.1574-6968.1999.tb08764.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of type I pili is abolished in verotoxin-producingEscherichia coliO157

Abstract: Verotoxin-producing Escherichia coli (VTEC) were examined for production of type I pili. None of 34 strains of VTEC serogroup O157 examined expressed any pili, whereas 26 strains of 27 VTEC serogroup O26 and seven strains of nine non-VTEC O157 produced type I pili. These VTEC strains were collected from sporadic human cases and cattle in Okinawa in 1997. The genes encoding the major structural component (FimA) and the adhesin (FimH) of type I pili were detected in all 70 strains examined. The inability to expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It has been shown that strains of seropathotype A isolates are unable to express type 1 fimbriae due to a 16-bp deletion in the regulatory switch region of fimA (52)(53)(54). Interestingly, 7 seropathotype A isolates were able to agglutinate yeast in a mannose-independent manner and were able to autoagglutinate ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that strains of seropathotype A isolates are unable to express type 1 fimbriae due to a 16-bp deletion in the regulatory switch region of fimA (52)(53)(54). Interestingly, 7 seropathotype A isolates were able to agglutinate yeast in a mannose-independent manner and were able to autoagglutinate ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies identified the type 1 fimbriae in the EHEC strains O26 and O118 (154) after having been genetically traced to other EHEC strains, including O157:H7, O157:H-, and O55- (155). Despite the presence of the coding regions in the genome of these strains, type 1 fimbriae expression was not observed in these EHEC strains.…”
Section: Other Fimbrial Adhesin Proteinsmentioning
confidence: 99%